Pengembangan Media ATM SIARI Dalam Belajar Literasi Finansial Pada Pendidikan Anak Usia Dini Di PAUD Al-Islam Riyadhul Irfan Kecamatan Kadungora Tingkat Usia 5-6 Tahun - Aliyah, Siti; Nurhakimah, Yunisa (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2024)
The background to this research was conducting initial observations on October 11 2023 at the AL-Islam Riyadhul Irfan PAUD institution located at Kp. Cikaso RT 02 RW 08 Rancasalak Kadungora Village, Garut Regency. In PAUD, the financial literacy skills of children aged 5-6 years are still relatively low.  This is proven by data during initial observations carried out by researchers where data on knowledge of children aged 5-6 years about the concept of money and skills to recognize various types of money Developed 53.84% = 7 people, eligible 46.15 = 6 capable people 0 Proficient 0. Literacy is very important for every individual, be it parents, teenagers, even young children. This research aims to develop ATM SIARI media as a medium for learning financial literacy for young children, as well as to determine the feasibility of ATM SIARI as a learning media in Early Childhood financial literacy. This research is an R&D research that adopts developments from Borg and Gall, the subjects in this research are PAUD Al-Islam Riyadhul Irfan aged 5-6 years and PAUD Sabilulungan aged 5-6 years with data collection instruments in the form of questionnaires validated by several experts, namely : material experts and media experts to test the quality of SIARI ATMs, several stages of testing were also carried out, namely: individual trials, small group trials, and large group trials to determine the quality of SIARI ATMs, the type of data produced was qualitative which was analyzed with guidelines for assessment criteria to determine the quality of the SIARI ATM Media being developed. This research produced a product in the form of ATM SIARI as a learning media based on research by material experts, getting an average score of 4 with a very precise category, the media expert's assessment got an average score of 3, with the correct category, assessment in individual trials, getting a pre-test score of 5.2. and the posttest score is 15, the SIARI ATM media has an influence on learning financial literacy for young children. Small group trials obtained a calculated T value that was greater than the t table, namely 53.97>1.710. So, there was a significant influence. And the large group trial obtained a calculated t value that was greater than the t table, namely 149.481>1.710 So there is a significant influence and the ATM SIARI media is suitable for use in learning financial literacy for early childhood. Keywords: SIARI ATM Media, Early Childhood, Financial Literacy